Differences in quality of life determinants according to the presence of fibromyalgia in middle‐aged female patients with systemic lupus erythematosus: a multicenter, cross‐sectional, single‐ethnicity cohort. (6th June 2018) - Moon, Su‐Jin; Kang, Kwi Young; Kwok, Seung‐Ki; Ju, Ji Hyeon; Hong, Yeon‐Sik; Park, Sung‐Hwan; Jeon, Chan Hong; Choi, Sang Tae; Song, Jung‐Soo; Min, Jun‐Ki
Abstract: Objective: The purpose of this study was to identify whether determinants of health‐related quality of life (HRQoL) in middle‐aged female patients with systemic lupus erythematosus (SLE) differed according to the presence or absence of fibromyalgia. Methods: One hundred and fifty‐two patients with SLE and 139 healthy controls (HCs) completed the Medical Outcomes Study 36‐Item Short Form (SF‐36) and EuroQol EQ‐5D questionnaires about HRQoL. Disease activity and cumulative disease damage were assessed with standard indices. Sleep quality was assessed using the Korean version of the Pittsburgh Sleep Quality Index (K‐PSQI). Result: The mean EQ‐5D and physical and mental components of SF‐36 were lower in SLE patients with fibromyalgia ( n = 41) than in those without fibromyalgia ( n = 111) and HCs. The scores in all eight domains of the SF‐36 were lower in SLE patients with fibromyalgia than in patients without fibromyalgia and HCs. Poor sleep (defined as a K‐PSQI > 5) was reported by 85% of SLE patients with fibromyalgia, by 51% of patients without fibromyalgia, and by 33% of HCs. Multivariate logistic regression analysis showed that lower educational level, cumulative organ damage severity and poor sleep quality were independent determinants of HRQoL in SLE patients with fibromyalgia, whereas disease activity, sleep quality and depressive mood were independent determinants of HRQoL in those without fibromyalgia. Conclusion: Poor sleep quality is the common independent risk factor for poor HRQoL in both middle‐aged SLE patients with fibromyalgia and without fibromyalgia. Sleep quality improvement may improve HRQoL in female SLE patients, even in those without fibromyalgia.